Protective effects of Cyclea barbata Miers leaves against aspirin-induced gastric ulcer in mice - Siregar, Iskandar Muda; Miladiyah, Isnatin (Universa Medicina, 2011)
One side effect of non-steroidal anti-inflammatory drugs is gastric mucosal irritation, possibly causing gastric ulcers. The aim of this study was to evaluate the protective effect of cincau leaves (Cyclea barbata Miers) on aspirin-induced gastric ulcer in Balb/c mice. Twenty five Balb/c mice (20-30 g, 2-3 months old) were randomly divided into 5 groups. Group I-III were given cincau leave infusion at dosages of 2.5 mg/kg BW, 5 mg/kg BW, and 10 mg/kg BW, respectively, while group IV (positive control) received antacid at a dosage of 20 mg/kg BW, and group V (negative control) one milliliter of distilled water. All interventions were given by the oral route, once daily for seven days. On day 7, the mice were given aspirin (600 mg/kg BW) to induce gastric ulcer. After 30 minutes, all mice were sacrified, and their stomachs examined macroscopically for gastric ulcer, characterized by the presence of ulcer(s) and bleeding. Total ulcer scores were analyzed by one-way Anova to compare between-group protective effect of interventions against aspirin-induced gastric ulcer. Results showed that groups treated with cincau leaf infusion at all dosages experienced a gastric ulcer protective effect. There were significant differences (p=0.002) between treatments, compared to the negative control, but no significant differences (p>0.05) when compared to the positive control. Thus cincau leaves (Cyclea barbata Miers) at dosages of 2.5 mg/kg BW, 5 mg/kg BW, and 10 mg/kg BW, had a protective effect against aspirin-induced gastric ulcer in mice. Higher dosages of cincau leaf infusion have a correspondingly higher gastric ulcer protective power.